Pengaruh Covid-19 Dalam Partisipasi Politik Pemuda Pada Pemilihan Kepala Desa Bulagidun Kecamatan Gadung Kabupaten Buol Tahun 2021 - Sutarni, Sutarni; Lukum, Roni; Mahmud, Ramli (Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of this study is (1). how the covid-19 impact on young men's participation in the election of bulagidun village chief, (2). what factors influence the political participation of young men in the election of bulagidun village's chief. The method used in this study is a type of qualitative research. the village headman election is a common process in every village. This was done to select new leaders to build and strengthen the village. Pilkades was a show where citizens could vote for future leaders. Because the election of kades was crucial because it helped run the village government. Village people can choose their future village leaders democratically. The influence of covid-19 in the political participation of young men in the 2021 bulagidun village, can be seen from the 3 aspects, the first contribution of young men to political rights (voting), shows that their conventional political participation was quite effective, but a number of young men from bulagidun did not vote for the village head, which was caused by the covid-19 pandemic situation. This is one of the problems with the implementation of these algorithms. According to the data, the participation rate of youth in determining his political rights is not high at the polls for village headmen, many of whom are either out of the area or working in the mines, so as not to give the vote.